Indebtedness and fiscal stability: Is history repeating itself? - Guillermo E. Perry (CEPAL Review, 1997)
Public indebtedness -and especially domestic indebtedness- is steadily increasing in a number of countries of the region, despite the major fiscal adjustment processes that have been carried out since the mid-1980s. This article analyses the main problems that this raises for public policy. It first reviews the question of the sustainability of public indebtedness. It then analyses the possible effects of privatization processes, the accumulation of indebtedness against assets, the increase in indebtedness not backed up by prior financing or contingent liabilities, the sustainability of the debt in terms of the acceptable level of inflation, the factors determining expectations regarding the sustainability oT fiscal policy and the effects of those expectations on interest rates and sustainable levels of indebtedness, and the extent to which the management of the debt affects its sustainability, and vice versa.